Atividade de morcegos em cinco hábitats de uma paisagem fragmentada de Floresta Atlântica do sul do Brasil - Suckow, Urubatan Moura Skerratt [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
We investigated the foraging activity of bats in five habitats in an Atlantic Forest landscape located in southern Brazil. Using mist-nets and ultrasound detectors, we tested the two hypotheses (Chapter I): (a) phyllostomids activity is highest in conserved forests than in degraded habitats (riparian area, city and monoculture); (b) aerial insectivorous activity (molossids and vespertilionids) is highest in open space habitats (city, riparian degraded area and monoculture) than narrow space habitats (submontane and riparian forest). The first hypothesis was confirmed, but the abundance and richness were similar in degraded riparian areas and conserved forests. Moreover, aerial insectivorous bats (molossids and vespertilionids) were more active in open habitats especially in the urban environment and degraded riparian areas supporting the second hypothesis. Using the same methods (mist-nets and ultrasound detectors), we evaluated (Chapter II) the “lunar phobia” on aerial insectivorous (molossids and vespertilionids) and frugivorous phyllostomids, considering the prediction that activity of the insectivorous are independent of the brightness of the moon (faster aerial foragers) while frugivorous are less activity during periods of more brightness (slowest foragers). The results indicated response variation related to the brightness just to phyllostomids, confirming the initial prediction. The data set for this dissertation demonstrates that four common phyllostomids (Artibeus lituratus, A. fimbriatus, Carollia perspicillata, Sturnira lilium) explore different environments in the region, including open plots as degraded riparian areas. These places seem to favor the activity not only some phyllostomids but also aerial insectivorous bats (molossids and vespertilionids) as sites to movement between forest patches or feeding areas. The variation in foraging activity of insectivorous and frugivorous phyllostomids seems related with the ...

Neste estudo nós investigamos a atividade de forrageio de morcegos em cinco hábitats com diferentes fisionomias localizados em uma paisagem de Floresta Atlântica alterada do sul do Brasil. Por meio de redes-de-neblina e detectores de ultrassom, nós testamos as seguintes hipóteses (Capítulo I): (a) a atividade dos filostomídeos é maior nas florestas conservadas do que em hábitats degradados (área aluvial, cidade e monocultura); (b) a atividade de molossídeos e vespertilionídeos (insetívoros aéreos) é maior nos hábitats fisionomicamente abertos (cidade, área aluvial degradada e monocultura) do que nos fechados (floresta submontana e floresta aluvial). A primeira hipótese foi confirmada, exceto para as áreas aluviais degradadas que representaram um valor similar de abundância e riqueza àqueles observados para as florestas conservadas. Morcegos insetívoros aéreos (molossídeos e vespertilionídeos), por sua vez, foram mais ativos nos hábitats abertos, com destaque para o ambiente urbano e áreas aluviais degradadas, confirmando a segunda hipótese do trabalho. Utilizando os mesmos métodos (redes-de-neblina e detectores de ultrassom), nós avaliamos (Capítulo II) a “fobia lunar” em insetívoros aéreos (molossídeos e vespertilionídeos) e filostomídeos frugívoros, valendo-nos da predição de que insetívoros mantêm sua atividade de forrageio independente da luminosidade da lua (forrageadores aéreos mais rápidos), enquanto frugívoros reduzem sua atividade em períodos de maior luminosidade (forrageadores mais lentos). Os resultados indicaram variação na resposta mediante o aumento da luminosidade apenas para filostomídeos, confirmando a predição inicial. O conjunto de dados desta dissertação demonstra que quatro filostomídeos comuns (Artibeus lituratus, A. fimbriatus, Carollia perspicillata, Sturnira lilium) exploram vários ambientes na região, incluindo parcelas fisionomicamente abertas, como áreas ...
Keywords: Ecologia animal; Morcego - Habitat; Morcego - Comportamento; Fobia lunar; Conservação biológica; Mata Atlântica Brasil, Sul; Bats